Design of a new multiplex PCR assay for rice pathogenic bacteria detection and its application to infer disease incidence and detect co-infection in rice fields in Burkina Faso - Bangratz, M.; Wonni, I.; Kini, K.; Sondo, M.; Brugidou, C.; Gilles, B.; Gnacko, F.; Barro, M.; Koebnik, R.; Silué, D.; Tollenaere, C. (Public Library of Science, 2020)
Crop diseases are responsible for considerable yield losses worldwide and particularly in sub-Saharan Africa. To implement efficient disease control measures, detection of the pathogens and understanding pathogen spatio-temporal dynamics is crucial and requires the use of molecular detection tools, especially to distinguish different pathogens causing more or less similar symptoms. We report here the design a new molecular diagnostic tool able to simultaneously detect five bacterial taxa causing important diseases on rice in Africa: (1) Pseudomonas fuscovaginae, (2) Xanthomonas oryzae, (3) Burkholderia glumae and Burkholderia gladioli, (4) Sphingomonas and (5) Pantoea species. This new detection tool consists of a multiplex PCR, which is cost effective and easily applicable. Validation of the method is presented through its application on a global collection of bacterial strains. Moreover, sensitivity assessment for the detection of all five bacteria is reported to be at 0.5 ng DNA by μl. As a proof of concept, we applied the new molecular detection method to a set of 256 rice leaves collected from 16 fields in two irrigated areas in western Burkina Faso. Our results show high levels of Sphingomonas spp. (up to 100% of tested samples in one field), with significant variation in the incidence between the two sampled sites. Xanthomonas oryzae incidence levels were mostly congruent with bacterial leaf streak (BLS) and bacterial leaf blight (BLB) symptom observations in the field. Low levels of Pantoea spp. were found while none of the 256 analysed samples was positive for Burkholderia or Pseudomonas fuscovaginae. Finally, many samples (up to 37.5% in one studied field) were positive for more than one bacterium (co-infection). Documenting co-infection levels are important because of their drastic consequences on epidemiology, evolution of pathogen populations and yield losses. The newly designed multiplex PCR for multiple bacterial pathogens of rice is a significant improvement for disease monitoring in the field, thus contributing to efficient disease control and food safety.